“Performing Emotions and Suffering.” Recovery of Depressive Symptoms Involving Adolescent Intervention in Art and Dance Schools - José Carlos SANTOS; Helena QUARESMA; Cláudia CARMO; Jorge FAÇANHA; António NABAIS; Lurdes SIMEÃO; Cláudia CALÇAS; Ermelinda MATOS; Isabel CORUCHE; Rosa SIMÕES; Maria ERSE; Cândida LOUREIRO; et al. (European Journal of Mental Health, 2022)
Introduction: In previous studies, a large majority of dance students reported mental health issues, mainly eating disorders and depression. Aims: This project aimed to promote mental health and well-being as well as prevent maladaptive and risky behaviors – namely suicidal behavior – among adolescents who attend art and dance schools. It was implemented in sequential stages, including six moments of classroom intervention for adolescents. Methods: A quasi-experimental research design was applied, with two assessment moments (before and after the intervention) using questionnaires filled out by the adolescents. Results: The project was implemented in three art schools (Center and South of Portugal), and the sample consisted of 122 adolescents. 72.9% of our sample were girls aged 12–18 years (M = 13.88; SD = 1.54). Boys showed significantly higher well-being scores (M = 16.53; SD = 4.24 vs M = 14.67, SD = 4.17), and girls showed higher coping scores (M = 153.3; SD = 13.53 vs M = 146.73; SD = 13.22). Concerning depressive symptoms, 34.8% of adolescents had moderate/severe depressive symptoms, which decreased by 10% after the intervention. Conclusions: Adolescents attending art schools might be more vulnerable to developing mental distress, and this intervention proved to be an effective approach for promoting mental health and well-being as well as preventing suicidal behaviors.